Asuhan Keperawatan Medikal Bedah Dengan Dengue Hemoragic Fever (DHF) Di Ruang Interne Rsud Prof. H. Muhammad Yamin S.H Pariaman - Afra Syavira Jolianda; Aulia Asman; Kheniva Diah Anggita; Mike Asmaria (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. This disease remains a public health concern; globally, there have been 14.6 million reported cases of Dengue Hemorrhagic Fever (DHF) with more than 11,000 deaths. In Indonesia, the incidence rate is quite high, reaching 131,393 cases with 544 deaths. West Sumatra recorded 88,593 cases, including in the city of Pariaman, which has geographical conditions conducive to vector development, recording 85 cases. Based on the data, DHF cases rank among the top 15 diseases at Prof. H. Muhammad Yamin Pariaman Regional General Hospital, accounting for 6.32% of cases. The objective of this study is to provide comprehensive nursing care for patients with DHF. This study employed a case study method with one patient in the internal medicine ward at Prof. H. Muhammad Yamin General Hospital in Pariaman from February 9–13, 2026, using the nursing process approach, which includes assessment, diagnosis, intervention, implementation, and evaluation. Data collection techniques included interviews, observations, physical examinations, and document review. The results of the study showed that the nursing diagnoses identified were hypovolemia, risk of bleeding, hyperthermia, and risk of nutritional deficit. The evaluation showed that hypovolemia improved on the 5th day, the risk of bleeding improved, and hyperthermia was resolved The patient’s fever peaked on the fourth day, and their nutritional status improved, as evidenced by an increased appetite. The patient is advised to maintain adequate fluid intake, get plenty of rest, and seek immediate medical attention if symptoms recur. Family members are encouraged to actively support the patient, practice good hygiene and healthy living habits, and prevent mosquito breeding in the home environment.